Associations of gender, race, and ethnicity with disparities in short‐term adverse outcomes after pancreatic resection for cancer. Issue 4 (16th November 2021) - Pastrana Del Valle, Jonathan; Mahvi, David A.; Fairweather, Mark; Wang, Jiping; Clancy, Thomas E.; Ashley, Stanley W.; Urman, Richard D.; Whang, Edward E.; Gold, Jason S.
Abstract: Background: Several studies have identified disparities in pancreatic cancer treatment associated with gender, race, and ethnicity. There are limited data examining disparities in short‐term adverse outcomes after pancreatic resection for cancer. The aim of this study is to evaluate associations of gender, race, and ethnicity with morbidity and mortality after pancreatic resection for malignancy. Methods: The American College of Surgeons National Surgical Quality Improvement database was retrospectively reviewed. The χ 2 test and Student's t ‐test were used for univariable analysis and hierarchical logistic regression for multivariable analysis. Results: Morbidity and major morbidity after pancreaticoduodenectomy are associated with male gender, Asian race, and Hispanic ethnicity, whereas 30‐day mortality is associated with the male gender. Morbidity and major morbidity after distal pancreatectomy are associated with the male gender. Morbidity after pancreaticoduodenectomy is independently associated with male gender, Asian race, and Hispanic ethnicity; major morbidity is independently associated with male gender and Asian race, and mortality is independently associated with Hispanic ethnicity. Conclusions: Gender, race, and ethnicity are independently associated with morbidity after pancreaticoduodenectomy for cancer; gender and race are independently associated with major morbidity; and ethnicity is independently associated with mortality. Further studies are warranted to determine the basis of these associations.